Meningkatkan Kemampuan Numerasi Matematika Siswa Melalui Pendekatan Problem-Based Learning - J. Lihawa, Ningsi; Zakaria, Perry; Kobandaha, Putri Ekawati (Research in the Mathematical and Natural Sciences, 2025)
This study aims to improve students' mathematical numeracy skills through the Problem Based Learning (PBL) approach. This research was conducted at SMK Negeri 1 Bonepantai in the 2024/2025 academic year. The subjects of this study were 13 class X-TKJ students. Data collection techniques used were observation and tests. The research instruments used were numeracy ability test instruments, instructor activity observation sheets, and student activity observation sheets. This study was conducted in two rounds. This is evident from the fact that teacher activities with good and very good criteria increased by 19.04 percent from 76.2% in cycle I to 95.24 percent in cycle II. Additionally, with high and very strong criteria, student activities rose by 41.14 percent from 47.06 percent in cycle I to 88.2 percent in cycle II. Additionally, students' arithmetic numeracy skills improved by 23.08 percent, rising from 6 1.54 percent in cycle I to 8 4.62% in cycle II. As a result, the action success indicator has been attained by the success indicators for teacher and student observation activities as well as the students' mathematical numeracy skills. Therefore, the use of the Problem Based Learning (PBL) model has been scientifically proven to improve the mathematical numeracy ability of Class X students of SMK Negeri 1 Bonepantai.